Strategi Penataan Penambangan Emas Skala Kecil di Karang Jaya, Musi Rawas Utara - Ummi Jayanti; Vera Surtia Bachtiar (Fakultas Teknik Universitas Cenderawasih, 2026)
Artisanal and small-scale gold mining (ASGM) provides short-term income for rural communities but frequently creates environmental, safety, and governance problems when it operates outside formal control. This study aimed to analyze the existing condition of ASGM, identify the driving and inhibiting factors of its arrangement, describe the perceived impacts, and formulate strategic directions for ASGM arrangement in Karang Jaya District, North Musi Rawas Regency, Indonesia. A qualitative descriptive approach was applied using semi-structured interviews supported by secondary data on the study area, population, and agricultural land use. Twenty-two informants represented district officials, village officials, technical agencies, company representatives, community leaders, nearby residents, and ASGM actors. Data were analyzed through reduction, presentation, interpretation, and conclusion drawing. The findings show that ASGM development is driven by gold potential, mining history, household economic pressure, limited alternative employment, and weak field control. The main impacts include land degradation, open mining pits, landslide and occupational accident risks, and mercury-related water and soil contamination. The recommended strategy combines alternative livelihood development, skills training, local economic institutional strengthening, gradual area monitoring, land rehabilitation, and mercury-risk education.